Fuzzy Logic Based Aeration Control System for Contaminated Water - Vijayakumar, T.; Vinothkanna, R.; Duraipandian, M. (Journal of Electronics and Informatics, 2020)
The waste water which are the outcomes of processing liquids cannot be used further without proper treatment so the water has to be treated and handled in order to elude the contamination that deteriorates the quality of the atmosphere. Although the biological methods can be utilized for treating the wastes in the water by decomposing the bacteria, it is biased by various causes such as the impurity level, the oxygen available, the dirt type etc. But the standard methodology like aeration utilizes the biological and the chemical oxygen demand reduction termed BO and CO respectively to treat the waste water, the conventional aeration process is performed manually causing enormous usage of electrical energy. So the paper elaborates the scheme of a fuzzy logic based aerator control system (FLACS) for the waste water. The essential equipment of the proposed system are the sensors providing the particulars of the chemical and the biological oxygen demand as input, the microcontroller (Arduino UNO) and other electrical and electronic equipment’s that controls the working of the aerator. The analysis performed on the proffered model indicates the performance improvement of the FLACS in terms of the electrical energy utilization and duration of working hours.